2020
DOI: 10.1177/0363546520915199
|View full text |Cite
|
Sign up to set email alerts
|

Does the Dog-Ear or Bird-Beak Deformity Remodel After Rotator Cuff Repair?

Abstract: Background: Dog-ear and bird-beak deformities are common after transosseous-equivalent repair (suture bridge technique). The natural course of deformities after rotator cuff (RC) repair using the suture bridge technique is unclear. The remodeling potential of these deformities has not been investigated. Purpose: To evaluate remodeling and retear rates associated with deformities after RC repair. Study Design: Cohort study; Level of evidence, 3. Methods: Between November 2011 and February 2012, we studied 99 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In cases with normal tendons, the re-tear sign on the rotator cuff tendon on MRI may be due to con guration deformities ((such as dog-ear deformity). Speci cally, most deformities after rotator cuff repair were remodeled and rotator cuff tendon coverage may improve with time [14,28]. Previously, Jin et al [29] found that three patients who were classi ed as Sugaya type III at three months after surgery appeared as Sygaya type II at one year postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with normal tendons, the re-tear sign on the rotator cuff tendon on MRI may be due to con guration deformities ((such as dog-ear deformity). Speci cally, most deformities after rotator cuff repair were remodeled and rotator cuff tendon coverage may improve with time [14,28]. Previously, Jin et al [29] found that three patients who were classi ed as Sugaya type III at three months after surgery appeared as Sygaya type II at one year postoperatively.…”
Section: Discussionmentioning
confidence: 99%